Assessing benefits and risks of online shopping in Spain and Scotland - Santana, S.; Loureiro, S. M. C. (Portuguese Journal of Management Studies, 2010)
The use of the Internet for shopping is increasing worldwide. Therefore, it has become very important to understand how consumers perceive its benefits and risks. In this paper, we address perceived benefits and risks of online shopping in Spain and Scotland. Building upon previous work done by others, athree-factor scale of perceived benefits and afour-factor scale of perceived risks were estimated. Women tend to perceive the enjoyment and adventure of online shopping more and are also more concerned with risks than men. Frequency of online searching correlates with perceived benefits and risks but its impact is different in the two countries. It is urgent to research the roles of emotion, interpersonal relationships and social involvement in conducting purchases online- an effort that will certainly require new models of consumer behavior and methodologies beyond the traditional quantitative techniques.